IMPLICATIONS OF HINDU-ISLAM WORSHIP PRACTICES AT PURA KRAMAT RATU MAS SAKTI MENGWI BADUNG - I Wayan Sukabawa; I Wayan Artayasa; I Made Wirajana (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2023)
The discourse of religious moderation is important in Indonesia. The recent condition of the nation which is vulnerable to conflicts in the name of religion is the cause. Indonesia as a country with high diversity both in terms of religion, ethnicity and customs and race is allegedly vulnerable to division. Thus, the moderate path is the only way to ensure Indonesia's unity and unity. Descriptively this work tries to narrate forms of religious life which are full of tolerance, moderation and mutual respect at Kramat Ratu Mas Sakti Temple, Mengwi Badung. The unique thing that happens in this temple is that Hindu and Muslim communities carry out religious activities in the same place and simultaneously. They worship according to their beliefs but are in the same place. This condition makes them look after each other and respect each other. Harmonious life is a priority and a shared need, so they try to work together for it. This is a form that might be offered to the Indonesian people, namely if you want a life of moderation to go well, then the need for the importance of coexistence is highly recommended.